Transformational leadership and creativity in sport: Examining the mediating role of support for innovation - Bosselut, G.; Guilbert, L.; Chareyre, L. (Journal of Sports Sciences, 2020)
Understanding how and when transformational leadership is related to followers` perceptions is an important issue. The present study aims to investigate the potential mediating role of support for innovation in the relationship between transformational leadership and creativity in team sports. We also propose that players` team tenure could moderate this relationship.